A new semi‐empirical equation for compressed liquid densities of n‐alkanes. Issue 3 (13th August 2012) - Sun, Yanjun; Wang, Xiaopo; Liu, Zhigang
ABSTRACT In this work, a new six‐parameter semi‐empirical equation has been developed for the predictions of the compressed liquid densities of n‐alkanes from C2 to C10. The resulting functional form was established with the quasi‐Newton optimization algorithm, which considers the experimental data sets for different fluids simultaneously. During the fitting process, the functional form of the equation is numerically very stable, and the substance‐specific coefficients can be obtained easily. The calculated values from the new model were compared with the available experimental data and the values from reference equations in the literature. In most cases, the deviations are not more than ±0.5% for temperatures up to 0.7 times the critical temperature, whereas the agreement is within ±1.0% in the temperature range from the triple point to the critical point at reduced pressure up to 15. It was shown that the new semi‐empirical equation was able to represent the compressed liquid densities of n‐alkanes in wide thermodynamic ranges. © 2012 Curtin University of Technology and John Wiley & Sons, Ltd.